Strategi Pemasaran Usaha Kecil Menengah Obat Herbal Tradisional Di Kota Palangka Raya - Nurhaliza; Erlina, Yuni; Mukti, Abdul; Zaki, Ahmad; Asiaka, Fandi K.P. (J-SEA (Journal Socio Economic Agricultural), 2026)
Marketing is an important activity for SMEs in pursuing sales targets and profit generation. There are various types of SMEs growing in Palangka Raya City, one of which is the Ratna Herbal Alami Dayak SME focusing on traditional herbal medicine business which has only been pioneered for three years. This research aims to help SMEs formulate appropriate marketing strategies to be able to compete with similar businesses. The strategy design is adjusted to the internal and external conditions. The case study research method, using descriptive qualitative SWOT analysis both internally and externally. The method of determining respondents uses key informants consisting of 12 people, namely the owner of the Ratna Herbal SME, Ratna Herbal employees, the Head of the Traditional Medicinal Plant Laboratory Section at the Central Kalimantan Provincial Health Office, and customers of Ratna Herbal. The results of the study that Ratna Herbal SMEs are in a WO strategy marketing strategy position, which has quite good opportunities. The strategies are minimizing internal problems to seize existing opportunities (turn-around strategy) such as improving the quality of raw materials, updating packaging, utilizing advances in information technology as a marketing strategy, distribution within the city can be reduced of chemical drugs and medical costs and maximizing sales outside Kalimantan through e-commerce to reduce weaknesses. Suggestions for owners to overcome weaknesses by taking care of the legal for halal certification and BPOM to guarantee safety, quality for consumers and with sharia, logo to encourage branding as a typical herbal medicine of Central Kalimantan.